Contingent Liabilities Risk Management : A Credit Risk Analysis Framework for Sovereign Guarantees and On-Lending - Bachmair, Fritz Florian (World Bank, Washington, DC, 2016)
Sovereign credit guarantees and government on-lending can catalyze private sector investment and fulfill specific policy objectives. However, contingent liabilities stemming from guarantees and contingent assets stemming from on-lending expose governments to risk. Prudent risk management, including risk analysis and measurement, can help identify and mitigate these risks. This paper proposes a four-step structure for analyzing and measuring credit risk: (i) defining key characteristics to determine the choice of a risk analysis approach; (ii) analyzing risk drivers; (iii) quantifying risks; and (iv) applying risk analyses and quantification to the design of risk management tools. This structure is based on an assessment of approaches discussed in academia and applied in practice. The paper demonstrates how the four steps of credit risk management are applied in Colombia, Sweden, and Turkey. It also discusses how the proposed framework is applied in Indonesia as it develops a credit risk management framework for sovereign guarantees.